A Study on Suicide Ideation among Medical Students in Mangalore (Indian Journal of Public Health Research & Development, 2020)
Introduction: Suicide is the second most common cause of death among adolescents in industrializedcountries and high rates are being reported from India recently. Objectives: To determine the prevalenceof suicidal ideation among students in a medical college in Mangalore and to associate the same withvarious socio demographic characteristics. Materials & Methods: A cross sectional (health survey) studydone using pre-validated, structured and self-administered questionnaire based on Beck’s scale of suicidalideation, elicits questions on demography, life events and suicide ideation. Universal sampling method wasfollowed and Chi Square test was done to test the significance (p
Keywords: Suicide, Stress, Isolation, Medical students, Beck’s scale, suicidal ideations